Optimalisasi Biaya Operasional Pembuangan Sampah di Perumahan Bontoramba Kabupaten Maros - Watono Watono (Departement of Mathematics Education, 2023)
The local population reaches around 322,212 people, maros regency produces large amounts of waste every result, the costs for waste management are increasing. Most of the waste is from population activities such as household waste, industrial waste, market waste, hospital waste, agricultural waste, plantation waste, agricultural waste, association / office / school waste, and so on ... More important than other types of diversity, including packaging waste that is more difficult and more difficult to decipher by natural processes. To strive to improve the quality of health in Bontoramba, both in terms of the influence of weather and air immersion, good management of waste disposal is needed. Both of the expenses from each house, each group of housing, blocks and the whole of the housing.The results of the interview analysis as many as 90.67% of the community were ready to receive contributions to the local government so that the waste in the location was wasted well or ready to dispose of the trash with the requirements to make temporary transfer places not to be far away because there were 82% of the community requested. need to be corrected systematically, both integrated, transport in order to overcome waste problems.